The curse of the cheese pyramid - Stilton, Geronimo (New York : Scholastic, 2004)
Geronimo Stilton travels from his home in New Mouse City to interview a famous Egyptian archaeologist and learns about pyramids, mummies, and hieroglyphs on a visit to the cheese pyramid.
Keywords: Mice -- Juvenile fiction; Humorous fiction